1989
DOI: 10.1080/10934528909375530
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potassium permanganate for inactivation of bacteriophage MS‐2 in water systems

Abstract: Potassium permanganate (KMnO 4 ) has been as an oxidant for decades to remove and control iron and manganese in surface water supplies. This oxidant was investigated for its ability to inactivate bacteriophage MS-2 and thereby reduce the amount of chlorine required for a 99.99% reduction of virus during drinking water treatment as required by the U.S. Environmental Protection Agency's Surface Treatment Rule (U.S. EPA 1989). Experiments * Corresponding Author 979 Copyright© 1989 by Marcel Dekker, Inc. Downloade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…With respect to (potassium) permanganate, it is a strong oxidizing agent used as an oxidant in in the pre-oxidation phase of a drinking-water treatment/production [433][434][435][436][437][438][439][440], as an algicide [441][442][443][444], and as a bactericide in treatment of bacterial fish diseases in fish culture ponds [445][446][447][448][449][450][451]. Deichmann and Gerarde [452] reported that potassium permanganate has a probable lethal adult dose of about 10 g. A recent EU substance evaluation document for Potassium permanganate [453] reported oral acute toxicity (LD 50 ) value of 1090 to > 2000 mg/kg of body weight and dermal acute toxicity (LD 50 ) value > 2000 mg/kg of body weight for potassium permanganate.…”
Section: Toxicity Concerns With Respect To Plausible Strategies For Mmentioning
confidence: 99%
“…With respect to (potassium) permanganate, it is a strong oxidizing agent used as an oxidant in in the pre-oxidation phase of a drinking-water treatment/production [433][434][435][436][437][438][439][440], as an algicide [441][442][443][444], and as a bactericide in treatment of bacterial fish diseases in fish culture ponds [445][446][447][448][449][450][451]. Deichmann and Gerarde [452] reported that potassium permanganate has a probable lethal adult dose of about 10 g. A recent EU substance evaluation document for Potassium permanganate [453] reported oral acute toxicity (LD 50 ) value of 1090 to > 2000 mg/kg of body weight and dermal acute toxicity (LD 50 ) value > 2000 mg/kg of body weight for potassium permanganate.…”
Section: Toxicity Concerns With Respect To Plausible Strategies For Mmentioning
confidence: 99%
“…Coliphage MS2 has been investigated as a potential indicator for contamination of water by sewage (7), for its sensitivity to disinfectants such as chlorine and ozone (2,8,13,14), and to help establish new viral models for human pathogens (4). When treated with some disinfectants, MS2 behaves similarly to poliovirus (6), reinforcing the idea of replacing the human enterovirus assays with MS2 for studying resistance mechanisms or the virucidal activity of biocides.…”
mentioning
confidence: 99%